Social media and drug resistance in nursing training: Using a Twitterchat to develop an international community of practice for antimicrobial resistance. Issue 13 (27th January 2020) - Wright, Rebecca; Ferguson, Caleb; Bodrick, Mustafa; Balkhy, Hanan; Jackson, Debra; Davidson, Patricia M.
Abstract: Aims and objectives: To assess the impact of a Twitterchat focusing on antimicrobial resistance and it is feasibility for integration within a nursing prelicensure research methods class. Background: Antimicrobial resistance is one of the greatest threats to global health and food security. Consequently, developing a global approach with large outreach is critical. Twitter, as a popular social media platform, is useful for creating communities of practice and communities of interest. Design: A case study design using a Twitterchat is a hosted, convened and focussed discussion on a particular topic using a discrete hashtag. Method: Using a standardised protocol, a Twitterchat was undertaken over a 24‐hr period and digital metrics assessed at 72 hr. A summary of impact was undertaken using an online tool provided by Union Metrics (https://unionmetrics.com/ ). Conclusions: At 72 hr, 2, 632, 762 accounts were reached and over 10 million impressions achieved. Twitterchats can be useful in creating awareness and fostering a community of interest and demonstrating the role of nurses in thought leadership. A formalised research study will draw on this case study to evaluate the impact on the Twitter participants and nursing students. Relevance to clinical practice: Social media are an accessible and useful tool to harness focus and attention on clinical issues with global relevance. Demonstrating the utility and leverage to nursing students is important in increasing their understanding of the importance of communication and diffusion of information.